The Role of Gis in Monitoring the Impact of Climate Fluctuations on The Decline of Surface Water Stored in The Mohamed V Dam on the Moulouya River (Eastern Region) - Amghar Ahmed; Sbai Abdelkader; Mouadili Omar (E3S Web of Conferences)
Water resources are not just a fundamental pillar of territorial development, but also a lifeline for all human economic and social activities. This necessity has led Moroccan officials to consider technical solutions to collect surface water, particularly in arid and semi-arid regions. Consequently, numerous dams have been constructed, forming significant infrastructure for water storage, with over 135 large and medium dams built by 2018. A new project was also initiated in early 2020 to construct more dams, underscoring the critical role of water resources in our daily lives. In recent years, the water reservoirs in arid and semi-arid regions, such as the lower Moulouya basin in northeastern Morocco, have been severely impacted by siltation. This is primarily due to the climatic characteristics of the region, marked by sudden and concentrated rainfall. The resulting water erosion, exacerbated by alternating periods of drought and continuous human pressure, has significantly reduced the storage capacity of the Mohamed V Dam from 730 million cubic meters at its inception to 327 million cubic meters. These observations, made using Geographic Information Systems (GIS), underscore the urgent need to address this issue.